D,A,B,C i think this is correct !
Answer:
![1\frac{9}{10}\ m](https://tex.z-dn.net/?f=1%5Cfrac%7B9%7D%7B10%7D%5C%20m)
Step-by-step explanation:
we know that
To find out how much more blue fabric than yellow fabric does Marcus need, subtract the quantity of yellow fabric from the quantity of blue fabric
step 1
Convert mixed number to an improper fraction
![3\frac{1}{10}\ m=\frac{3*10+1}{10}=\frac{31}{10}\ m](https://tex.z-dn.net/?f=3%5Cfrac%7B1%7D%7B10%7D%5C%20m%3D%5Cfrac%7B3%2A10%2B1%7D%7B10%7D%3D%5Cfrac%7B31%7D%7B10%7D%5C%20m)
![1\frac{1}{5}\ m=\frac{1*5+1}{5}=\frac{6}{5}\ m](https://tex.z-dn.net/?f=1%5Cfrac%7B1%7D%7B5%7D%5C%20m%3D%5Cfrac%7B1%2A5%2B1%7D%7B5%7D%3D%5Cfrac%7B6%7D%7B5%7D%5C%20m)
step 2
Subtract the numbers
![\frac{31}{10}-\frac{6}{5}=\frac{31}{10}-\frac{12}{10}=\frac{19}{10}\ m](https://tex.z-dn.net/?f=%5Cfrac%7B31%7D%7B10%7D-%5Cfrac%7B6%7D%7B5%7D%3D%5Cfrac%7B31%7D%7B10%7D-%5Cfrac%7B12%7D%7B10%7D%3D%5Cfrac%7B19%7D%7B10%7D%5C%20m)
Convert to mixed number
![\frac{19}{10}\ m=\frac{10}{10}+\frac{9}{10}=1\frac{9}{10}\ m](https://tex.z-dn.net/?f=%5Cfrac%7B19%7D%7B10%7D%5C%20m%3D%5Cfrac%7B10%7D%7B10%7D%2B%5Cfrac%7B9%7D%7B10%7D%3D1%5Cfrac%7B9%7D%7B10%7D%5C%20m)
Answer:
Yes.
Step-by-step explanation:
![f(g(x))](https://tex.z-dn.net/?f=f%28g%28x%29%29)
( I will have to replace all
's in
with
)
![9(\frac{x-12}{9})+12](https://tex.z-dn.net/?f=9%28%5Cfrac%7Bx-12%7D%7B9%7D%29%2B12)
![(x-12)+12](https://tex.z-dn.net/?f=%28x-12%29%2B12)
![x-12+12](https://tex.z-dn.net/?f=x-12%2B12)
![x+(-12+12)](https://tex.z-dn.net/?f=x%2B%28-12%2B12%29)
![x+0](https://tex.z-dn.net/?f=x%2B0)
![x](https://tex.z-dn.net/?f=x)
So the answer is yes.
- Here, both the triangles have equal sides.
- So, the two triangles are related by SSS.
- If all the sides of a triangle are equal to all the sides of another triangle, so the triangles are congruent to each other.
<u>Answer</u><u>:</u>
<u>SSS,</u><u> </u><u>congruent.</u>
Hope you could get an idea from here.
Doubt clarification - use comment section.
From cosine law
c^2 = a^2 + b^2 -2abcos(C)
cos(C) = (a^2 + b^2 - c^2)/2ab
this formula will solve your problem